The Effect of Magnetization Defects on DW Motion in Ferromagnetic Nanowires - Kimminau, Kyle; Kunz, Andrew (Proceedings of the Wisconsin Space Conference, 2011)
The propagation of domain walls in ferromagnetic nanowires offers the possibility of ultrafast logic devices and high density data storage. The understanding and control of domain wall motion has become more desirable recently as these devices come closer to realization. Domain walls can only be propagated by small magnetic fields or their movement becomes hindered by the precessional motion of the magnetic dipoles, also called the Walker breakdown effect1. Through the use of Landau-Lifshitz Gilbert Simulation, we report a method of eliminating the Walker breakdown. This investigation also offers some insight into how these proposed devices might perform in the high energy radiation of space for extended periods of time.Â